ANALISIS KUALITAS AIR DAN BEBAN PENCEMAR DI SUNGAI BATU KAMBING, SUNGAI MALI-MALI DAN SUNGAI RIAM KIWA KECAMATAN ARANIO KABUPATEN BANJAR KALIMANTAN SELATAN - Chiptya Adhey Noumy; Zairina Yasmi; Abdur Rahman (Faculty of Fisheries and Marine Resources of Lambung Mangkurat University-South Kalimantan, 2019)
This study aims to determine the water quality of the activities Keramba JaringApung (KJA) based on Pollutant Index and Air Quality Standard Quality specified in PP.82/2001 on Watershed of Batu Kambing, Riam Kiwa and Mali-Mali.This study uses pollutant load analysis and Pollutant Index based Kep.MenLH No.115 of 2003, Kep.MenLH No. 110/2003 on Based Determination of Water Pollution loadon Water Resources and laboratory analysis.From the research results Pollutant Load (BP) of each - each station are: Station 1(Batu Kambing) PO4 levels ranging from 0.40 kg/day and NO3 ranging from 0.36 kg/day.Station 2 (Riam Kiwa) for PO4 levels ranging from 0.42 kg/day and NO3 ranging from 0,012 kg/day. Station 3 (Mali – Mali river) PO4 levels ranging from 1.27 kg/day, whileNO3 ranging from 0.11 kg/day. Batu Kambing river, Riam Kiwa and Mali – Mali rivers included in the category of lightly polluted.